Military professionalism and humanitarian law : the struggle to reduce the hazards of war - Beer, Yishai, 1956- (New York, NY : Oxford University Press, 2018)
This work challenges the unacceptable gap between the positive rules of the international law governing armed hostilities and actual state practice. It discusses reducing the human suffering caused by this reality. The text offers a new paradigm based on reality that may elevate the humanitarian threshold by replacing the currently problematic imperatives imposed upon militaries with professionally-based, attainable requirements.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 5, 2018).
Keywords: War (International law); Self-defense (International law); Just war doctrine; Humanitarian law; Law; International law